Vulnerabilities, Insecurities and Discrimination of Women Workers: Ethnography and Reflections. - Kalpagam, U. and Narayan, Binod (2006)
This paper has two parts. The first part is ethnographic and based on fieldwork done by the first author and the second part deals with the issues highlighted in recent literature. Put together it seeks to provide a comprehensive account of the vulnerabilities, insecurities and discrimination that women workers face because of globalisation. Methodologically, the paper’s strengths are twofold. First, it argues that the impact of globalisation is uneven across regions and groups. Second, it argues for an analysis that moves beyond the use of well-worn administrative categories of labour market analysis towards evolving more appropriate social categories that provide better insights into the labouring worlds. The overwhelmingly negative analysis of globalisation effects in terms of livelihood insecurities has masked the simultaneous processes of rejuvenation in certain regions and the immense lifestyle changes that have occurred. Even understanding the varied nuances of vulnerabilities, insecurities and discrimination in the changed context, requires us to take cognisance of lifestyle changes not just at one end of the spectrum in terms of destruction of traditional livelihoods but the changes at the opposite end as well.